The Role Of The Police In Eradicating Illegal Gold Mining Activities In Pohuwato Regency - Sulistianingsi Buyu (Estudiante Law Journal, 2019)
AbstractThis Study aims to find out and analyze how law enforcement against perpetrators of gold mining activities without a permint in the pohuwato regency area is law enforcement against gold mining activities in pohuwato regency, not yet effective, because based on the results of the study it was found that there were 33 active tools, in illegal mining, which is suspected to belong to a dozen people but has not been processed by law to this day. This is contrary to article 158 of law no. 4 of 2009 concerning mining. To overcome the problems that occur as described in the discussion, researhers recommend a solution, namely law enforcement related to illegal mining activities in pohuwato regency needs to be emphasized, this is in order, so that no more people dare to carry out mining activaties illegaly and violate law. The local government of pohuwato regency, needs to pay more attention to mining activities by the people of pohuwato regency, by issuing people’s mining area (WRS) and mining busines permits (IUP), thus is important so that people are not trapped in mining activites that violate the law and pollute the environment, besides the existence of IUP and WPR can improve the economy of the people of pohuwato.Keywords: Law, Mining, Illegal